Amoxicillin loaded hollow microparticles in the treatment of osteomyelitis disease using single-nozzle electrospinning - Altun, Esra; Aydoğdu, Mehmet Onur; Koç, Fatma; Kutlu, Özlem; Gözüaçık, Devrim; Yücel, Sevil; Gündüz, Oğuzhan (Springer, 2018)
In this study, hollow microparticles were produced with polymethylsilsesquioxane/chitosan/bovine hydroxyapatite/hexagonalboron nitride (PCBB) polyblend using single-nozzle electrospinning method. Also, hollow microparticles are loaded withamoxicillin (AMX) and their drug delivery capabilities have been studied according to a treatment of osteomyelitis disease.The morphology, chemical groups, particle size, antimicrobial activity, and AMX drug release were systematically studied usingscanning electron microscopy (SEM), optical microscopy, Fourier transformation infrared spectroscopy (FTIR), hollow microparticle size measurements, antimicrobial activity test, and UV spectroscopy. In vitro biocompatibility was analyzed with humanbone osteosarcoma (U2OS) cell line. This present work can help in the design of a drug delivery platform for antimicrobial effectand bone repair at the same time for osteomyelitis disease treatment.
WOS: 000444750500009
Keywords: Single-Nozzle Electrospinning; Hollow Microparticles; Osteomyelitis; Drug Delivery; Bone Tissue Engineering